Ablation of apparent diffusion coefficient hyperintensity clusters in mesial temporal lobe epilepsy improves seizure outcomes after laser interstitial thermal therapy. Issue 3 (12th January 2023) - Kim, Min Jae; Hwang, Brian; Mampre, David; Negoita, Serban; Tsehay, Yohannes; Sair, Haris; Kang, Joon Y.; Anderson, William S.
Abstract: Objective: Laser interstitial thermal therapy (LiTT) is a minimally invasive surgical procedure for intractable mesial temporal epilepsy (mTLE). LiTT is safe and effective, but seizure outcomes are highly variable due to patient variability, suboptimal targeting, and incomplete ablation of the epileptogenic zone. Apparent diffusion coefficient (ADC) is a magnetic resonance imaging (MRI) sequence that can identify potential epileptogenic foci in the mesial temporal lobe to improve ablation and seizure outcomes. The objective of this study was to investigate whether ablation of tissue clusters with high ADC values in the mesial temporal structures is associated with seizure outcome in mTLE after LiTT. Methods: Twenty‐seven patients with mTLE who underwent LiTT at our institution were analyzed. One‐year seizure outcome was categorized as complete seizure freedom (International League Against Epilepsy [ILAE] Class I) and residual seizures (ILAE Class II–VI). Volumes of hippocampus and amygdala were segmented from the preoperative T1 MRI sequence. Spatially distinct hyperintensity clusters were identified in the preoperative ADC map. Proportion of cluster volume and number ablated were associated with seizure outcomes. Results: The mean age at surgery was 37.5 years and the mean follow‐up duration was 1.9 years. Proportions of hippocampal cluster volume ( p  = .013) and number ( p  = .03) ablated were significantly higher in patients with seizure freedom. For amygdala clusters, the proportion of cluster number ablated was significantly associated with seizure outcome ( p  = .026). In the combined amygdalohippocampal complex, ablation of amygdalohippocampal clusters reliably predicted seizure outcome by their volume ablated (area under the curve [AUC] = 0.7670, p  = .02). Significance: Seizure outcome after LiTT in patients with mTLE was associated significantly with the extent of cluster ablation in the amygdalohippocampal complex. The results suggest that preoperative ADC analysis may help identify high‐yield pathological tissue clusters that represent epileptogenic foci. ADC‐based cluster analysis can potentially assist ablation targeting and improve seizure outcome after LiTT in mTLE.